2018
DOI: 10.1186/s12985-017-0916-0
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Poyang lake water for sewage contamination using human enteric viruses as an indicator

Abstract: BackgroundRecreational water contaminated with fecal pollution poses a great public health concern, as fecal waste may cause serious waterborne illnesses. Current recreational water standards using fecal indicator bacteria (FIB) have their limitations for human protection especially in developing countries such as China.MethodsTo explore the potential use of enteric viruses as a potential indicator of fecal contamination, four viruses: norovirus geno-groups I and II, enteroviruses, and adenoviruses were tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…For the upstream and downstream sites based on the unintentional consumption of 1 mL or the deliberate consumption of 100 mL of river water, the results showed that the annual Pi with pathogenic E. coli was above that recommended for potable water [10,4] by the WHO [42]. The Pi was significantly higher in the upstream site than downstream site assuming exposure to either a 1 mL or 100 mL volume, implying that communities upstream of the WWTP were at greater risk of infection.…”
Section: Probability Of Infection With E Coli Following Exposure To mentioning
confidence: 93%
See 1 more Smart Citation
“…For the upstream and downstream sites based on the unintentional consumption of 1 mL or the deliberate consumption of 100 mL of river water, the results showed that the annual Pi with pathogenic E. coli was above that recommended for potable water [10,4] by the WHO [42]. The Pi was significantly higher in the upstream site than downstream site assuming exposure to either a 1 mL or 100 mL volume, implying that communities upstream of the WWTP were at greater risk of infection.…”
Section: Probability Of Infection With E Coli Following Exposure To mentioning
confidence: 93%
“…Faecal contamination of water with pathogenic bacteria, viruses, and protozoa remains one of the main causes of waterborne diseases as these microbes can persist in polluted water for protracted periods and ultimately cause infections [3,4]. Fecal contamination of water is mainly assessed using fecal indicator bacteria such as Escherichia coli and enterococci [5].…”
Section: Introductionmentioning
confidence: 99%
“…This leads to the failure in assessing the occurrence of enteric viruses in surface water, which may be another important consideration for why viral contamination in water has been overlooked [ 15 ]. This is the case even where bacterial indicators are currently used in most countries around the world for assessment of fecal or pathogen contamination in surface water [ 16 ]. In such settings, it is essential to explore a sensitive indicator that sufficiently expedites an early warning system relating to the occurrence of enteric viruses, which enables corrective action to be applied in a timely manner in regions with enteric virus-contaminated waters.…”
Section: Introductionmentioning
confidence: 99%
“…Urbanization and extreme weather events such as floods and wet/dry weather overflows result in an increased amount of sewage being discharged into water bodies (3,(25)(26)(27). Sewage-contaminated water bodies are potential public health hazards and can cause severe illnesses to humans due to the presence of infectious pathogens (28).…”
mentioning
confidence: 99%